Análisis del comportamiento de compra de servicios de entretenimiento en la ciudad de Cali (2018)
The objective of this paper is to identify the variables that intervene in the behavior of the consumer's purchase when deciding on a product or service, the behavior of the consumer refers to a series of physical and mental activities that each individual seeks to satisfy. a necessity through a choice, in this process different factors influence stories such as: cultural, personal, psychological and social. To carry out this objective, an instrument (survey) was applied to a representative sample of the company's target population, calculated under statistical parameters, which focuses on customer service strata 5 and 6 of the city of Santiago de Cali. Finally, the analysis of the information collected through the survey is carried out in order to suggest to the company POPS RECREACIÓN, different marketing strategies, which can improve its service portfolio and expand its participation in the Cali market